[ReF6]2−: A Robust Module for the Design of Molecule‐Based Magnetic Materials1. (21st January 2014) - Pedersen, Kasper S.; Sigrist, Marc; Sørensen, Mikkel A.; Barra, Anne‐Laure; Weyhermüller, Thomas; Piligkos, Stergios; Thuesen, Christian Aa.; Vinum, Morten G.; Mutka, Hannu; Weihe, Høgni; Clérac, Rodolphe; Bendix, Jesper
Abstract A facile synthesis of the [ReF6]2− ion and its use as a building block to synthesize magnetic systems are reported. Using dc and ac magnetic susceptibility measurements, INS and EPR spectroscopies, the magnetic properties of the isolated [ReF6]2− unit in (PPh4)2[ReF6]⋅2 H2O (1) have been fully studied including the slow relaxation of the magnetization observed below ca. 4 K. This slow dynamic is preserved for the one‐dimensional coordination polymer [Zn(viz)4(ReF6)]∞ (2, viz=1‐vinylimidazole), demonstrating the irrelevance of low symmetry for such magnetization dynamics in systems with easy‐plane‐type anisotropy. The ability of fluoride to mediate significant exchange interactions is exemplified by the isostructural [Ni(viz)4(ReF6)]∞ (3) analogue in which the ferromagnetic NiII–ReIV interaction (+10.8 cm−1) dwarfs the coupling present in related cyanide‐bridged systems. These results reveal [ReF6]2− to be an unique new module for the design of molecule‐based magnetic materials.